Assessment of Undiscovered Oil and Gas in the Arctic - Gautier, Donald L; Bird, Kenneth J; Charpentier, Ronald R; Grantz, Arthur; Houseknecht, David W; Klett, Timothy R; Moore, Thomas E; Pitman, Janet K; Schenk, Christopher J; Schuenemeyer, John H; Sørensen, Kai; Tennyson, Marilyn E; et al. (Science (American Association for the Advancement of Science), 2009)
Among the greatest uncertainties in future energy supply and a subject of considerable environmental concern is the amount of oil and gas yet to be found in the Arctic. By using a probabilistic geology-based methodology, the United States Geological Survey has assessed the area north of the Arctic Circle and concluded that about 30% of the world's undiscovered gas and 13% of the world's undiscovered oil may be found there, mostly offshore under less than 500 meters of water. Undiscovered natural gas is three times more abundant than oil in the Arctic and is largely concentrated in Russia. Oil resources, although important to the interests of Arctic countries, are probably not sufficient to substantially shift the current geographic pattern of world oil production.